Geochemical factors influencing the phosphorus mobility in Konza prairie grassland and agriculture-dominated soils in north-eastern Kansas - Banerjee, Protik; Kulkarni, Harshad V.; Veach, Allison M.; Nagaraja, Thiba; Pathak, Pousali; Das, Suprem R.; Datta, Saugata (Frontiers in Environmental Science, 2025)
IntroductionThe availability and mobility of phosphorus (P) in soils play a crucial role in effectively managing agricultural activities and maintaining healthy soils. Several parameters including soil texture, pH, elemental and mineralogical composition, moisture content, and soil organic matter (SOM) are crucial in controlling the movement of P in soils. This study focuses on assessing geochemical properties of soils from a pristine prairie grassland and an agriculturally dominated land, and their influence on soil P mobility.MethodsSurface soils were collected from two locations, Konza Prairie Biological Station (KBPS) located in Manhattan (Kansas) which is a native grassland ecosystem, and agricultural land in town of Hays (Kansas).ResultsResults showed that the KPBS soils contained lower water-extractable phosphate (PO43—) concentrations (0.2 ± 0.7 mg/kg) than soils from Hays (1.3 ± 2.4 mg/kg). Bio-available P measured as Bray-P were also lower in KPBS (14.3 ± 7.0 mg/kg) relative to Hays (23.0 ± 23.7 mg/kg). Soils from both the sites contained water-extractable calcium, magnesium and potassium as a primary soluble component likely from carbonate minerals in these calcareous soils. The SOM concentrations measured as loss on ignition (LoI) were greater in KPBS (9.9% ± 1.8%) relative to Hays (5.3% ± 1.7%). Water extractable soil organic carbon (WE-SOC) concentrations were also greater for KPBS (651 ± 274 mg/kg) relative to Hays (288 ± 267 mg/kg). Optical spectroscopic analyses using absorbance and fluorescence properties revealed that the water-extractable SOM in these soils was mainly of terrestrial origin, plant-derived, aromatic, and contained humic-like substances. The intensities of fluorescence peaks A, C, and M, and specific UV absorbance at 254 nm (SUVA 254) of both soils correlate strongly with the Bray-P concentrations, indicating that the source of SOM plays a vital role in controlling soil P mobility.ConclusionThese findings indicate that natural prairie grassland soils contained lower P concentrations that are primarily insoluble in water and associated with humic and fulvic-like SOM.